Enhancing Precision Agriculture Through a Spatial Correlation Analysis of Subsidized NPK Fertilizer Distribution and National Soil Nutrient Deficiencies - Anwa Robbo; Fransin Polnaya; Suleyman; Sevindrajuta; Zuyasna (Agriculture Journal, 2026)
This study addresses the critical structural misalignment between national fertilizer distribution policies and biophysical soil nutrient realities across the Indonesian archipelago. Utilizing a quantitative explanatory design, the research integrates large-scale secondary datasets from PT Pupuk Indonesia's logistics and the national soil hara maps of 514 districts to evaluate allocation efficiency. Spatial correlation analysis and the Nutrient Gap Index (G) were employed to identify systemic distribution anomalies. Findings reveal a profound disparity where nutrient-saturated regions, particularly in Java, exhibit significant over-supply (G reaches 0.90), while marginal agricultural frontiers in outer islands face acute deficits (G as low as -0.53). This imbalance correlates with a national Nutrient Use Efficiency (NUE) stagnation below the 40% threshold, signaling an environmental and fiscal plateau. The study concludes that the conventional "one-size-fits-all" distribution paradigm is no longer sustainable. We propose a strategic shift toward Site-Specific Nutrient Management (SSNM) by integrating geospatial soil data into the e-RDKK digital platform. These results advance the understanding of precision agriculture in tropical developing nations, establishing that food security depends on localized allocation precision rather than volumetric sufficiency.